Cerebrotendinous xanthomatosis: a literature review and case study - Matta, Anthony; Ory Magne, Fabienne; Levade, Thierry; Bonneville, Fabrice; Ferrières, Jean (Frontiers in Cardiovascular Medicine, 2024)
Cerebrotendinous xanthomatosis (CTX) is a rare but treatable inherited neurometabolic disorder that can lead to severe sequelae if left untreated. Chenodeoxycholic acid is a safe and effective treatment for CTX. Early diagnosis is essential to improve patient outcomes. Neurological disturbances, cataracts, and intractable diarrhea are key features to raise diagnostic suspicion and differentiate CTX from other metabolic disorders in patients with dyslipidemia and xanthomas. The diagnosis of CTX depends on high cholestanol plasma levels, undetectable plasma bile acids, neuroradiological findings, and CYP27A1 gene analysis. This review provides a stepwise approach to diagnosing patients with CTX, aims to improve physician awareness of CTX, and highlights the effectiveness of chenodeoxycholic acid as the standard of care. In addition, we report a unique case of CTX with major premature cardiovascular events, initially misdiagnosed as heterozygous familial hypercholesterolemia. This review also provides evidence to establish the c.470T>C (p. Leu157Pro) variant of the CYP27A1 gene as a likely pathologic variant.